Points saillants sur la santé mentale des jeunes franco-canadiens d’est en ouest du pays : le témoignage de nos assistantes de recherche - Benoit, Monique; Beaton, Ann. M. (Minorités linguistiques et société, 2018)

Instantané de recherche : l’avantage surprenant des jeunes francophones touchées par la dépression - CAMH-Evidence Exchange Network (2020)
Cet Instantané de recherche résume l’article intitulé « Les enjeux intersectionnels de la demande de services de santé mentale au Canada : La situation des jeunes femmes dépressives francophones », publié dans la Revue canadienne de service social en 2018.

Disponibilité et accessibilité des services de santé en français au Manitoba. Rapport final - de Moissac, Danielle; de Rocquigny, Janelle; Roch-Gagné, Margaux; Giasson, Florette (Université de Saint-Boniface et Institut franco-ontarien de l’Université Laurentienne, 2011)

Accès aux services sociaux et de santé en français : l’expérience des Franco-Manitobains - de Moissac, Danielle; Giasson, Florette; Roch-Gagné, Margaux (Minorités linguistiques et société / Linguistic Minorities and Society, 2015)
Des progrès considérables sont constatés dans l’offre de services et la formation de professionnels dans le domaine des services sociaux et de santé en français au Manitoba depuis les 30 dernières années. L’objectif de cette recherche est de mieux connaître la perception des usagers quant aux services couramment disponibles et aux barrières réduisant l’accès à ces services. L’obtention de services en français est importante pour la population francophone, particulièrement pour les aînés et les immigrants. En moyenne, 50 % des répondants disent demander des services en français, mais seulement 25 % affirment les recevoir. La pénurie de professionnels pouvant offrir des services en français est considérée comme la barrière principale à l’accès. L’offre active est essentielle et facilite la prestation des services dans la langue de choix de la clientèle. Mots-clés : accessibilité, santé, services sociaux, Manitoba, minorité francophone

Healthcare Service Utilization and Perceived Gaps: The Experience of French-Speaking 2S/LGBTQI+ People in Manitoba - de Moissac, Danielle; Prada, Kevin; Gueye, Ndeye Rokhaya; Avanthay-Strus, Jacqueline; Hardy, Stephan (Healthcare Policy, 2024)
Ethnolinguistically diverse 2S/LGBTQI+ (two-spirit, lesbian, gay, bisexual, transgender, queer and intersex) populations have unique healthcare needs and experience health inequities compared to their cisgender or heterosexual peers. This community-based participatory study sought to describe the profile and healthcare needs and experiences of official language minority French-speaking 2S/LGBTQI+ adults in Manitoba. Participants (N = 80) reported that gender and sexual identity were often concealed from service providers; many respondents faced discrimination based on their ethnolinguistic and sexual identities. Service gaps are identified pertaining to mental and sexual health; locating 2S/LGBTQI+-friendly, patient-centred care in French is difficult. Policy and practice should address systemic inequity and discrimination experienced by this equity-seeking population.

Health status of minority Francophone seniors in Manitoba and access to services in french: Potential for social isolation - de Moissac, Danielle; Roch-Gagné, Margaux; Ba, Halimatou; Gueye, Ndèye Rokhaya; Ethier, Sophie (Human Development, Disability, and Social Change, 2016)
Francophone seniors in Manitoba represent a growing and vulnerable population, with poorer health outcomes and limited access to health and social services in the official minority language. To avoid isolation, support services are required, as chronic diseases and reduced mobility have a direct impact on both physical and social needs. The purpose of this study is to examine the current health status of seniors in the Francophone minority population of Manitoba and their access to health and social services in French. Demographic, social and health profiles were obtained for Francophone and non-Francophone Home Care clients in Winnipeg. Although diagnosed with similar health conditions as non-Francophones, Francophone seniors are less likely to be assessed with reduced cognitive performance and conditions making mood and behaviour unstable, such as dementia other than Alzheimer’s. Gaps in bilingual health services were identified for pharmacy, audiology and occupational therapy services, meal and transportation systems as well as support services for informal caregivers. Housing options with in-house support services provided in French are available and additionally provide opportunities for seniors to socialize with other Francophones. For the elderly living in singlehome units and their caregivers, support services provided in the official minority language are needed. Keywords: seniors, health, Francophone minority, home care

Barriers to HIV care among Francophone African, Caribbean and Black immigrant people living with HIV in Canada: A protocol for a scoping systematic review - Djiadeu, Pascal; Nguemo, Joseph; Mukandoli, Chantal; Odhiambo, Apondi. J.; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2019)
Introduction Language is a social determinant of health. Addressing social determinants of health is paramount to successful progression along the HIV-care continuum. Canada is a bilingual country with French and English as official languages. There are few studies to date that have focused on the impact of being a French-speaking linguistic minority on the HIV-care continuum. The primary objective of this scoping, systematic review of literature is to evaluate existing gaps in access to HIV- care among French-speaking people living with HIV in Canada. Our primary outcome is healthcare services availability and access for French- speaking people living with HIV. Methods and analyses Our scoping, systematic review will draw on a systematic search of published literature, both quantitative and qualitative studies published on French-speaking individuals' healthcare and HIV status in Canada, with particular emphasis on the province of Ontario. We will conduct our search in MEDLINE, the Excerpta Medica Database, the Cumulative Index to Nursing and Allied Health Literature, Web of Science, EBSCO and Google Scholar for work published between 1990 and 2018. Identified articles will be screened in duplicate and full-text articles of relevant studies will be retrieved. Data will also be extracted by two researchers working independently. Any discrepancies that arise will be resolved by consensus or by consulting a third author. Our findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ethics and dissemination Our proposed research will not be conducted with human participants. We will only use secondary published data and therefore ethics approval is not required. Our findings will be disseminated as peer reviewed manuscripts at conferences and student rounds, and could be of interest to government health agencies and local HIV/AIDS service organisations.

Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

Améliorer l’accès des personnes âgées de Saint-Boniface et de Saint-Vital aux services de santé en français. Objectif 5 - Description des expériences de trajectoires individuelles de soins de santé en français pour les aînés | Improving St. Boniface and St. Vital seniors' access to French-language health services. Objective 5 - Description of experiences of seniors' individual trajectories in French-language health care - Éthier, Sophie; Ba, Halimatou; Belzile, Louise; Gagné, Maryanne; Roch-Gagné, Margaux (Conseil communauté en santé du Manitoba et Université de Saint-Boniface, 2012)

L’accès aux services de santé en français et leur utilisation en contexte francophone minoritaire. Rapport final - Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques et Société Santé en français, 2014)

Les enjeux intersectionnels de la demande de services de santé mentale au Canada : la situation de jeunes femmes dépressives francophones - Gaborean, Florina; Negura, Lilian; Moreau, Nicolas (Revue canadienne de service social, 2018)
Dans cet article, nous présentons, selon le cadre théorique féministe intersectionnel, une étude visant à mieux comprendre les dynamiques identitaires qui influencent la demande de services de santé mentale des jeunes femmes francophones vivant en situation minoritaire ainsi que les effets croisés de celles-ci sur les facteurs déclencheurs de la dépression, la perception des symptômes et le parcours thérapeutique. Notre analyse révèle que l’imbrication de plusieurs catégories d’inégalité complexifie l’accès aux services de santé mentale des jeunes femmes dépressives en situation minoritaire tout en favorisant l’émergence de stratégies de lutte et de résistance. Le croisement des catégories identitaires de genre, d’âge et de langue parlée produit des effets compensatoires sur la demande de services de santé mentale. Alors que l’image sociale positive de la jeunesse les fait hésiter dans la demande de services, celle liée à l’identité féminine légitime, la dépression et les faiblesses qui pourraient en découler. Les femmes mettent en oeuvre des stratégies pour pallier les inégalités d’accès aux services de santé mentale en français et trouver les services qu’elles considèrent appropriés pour leur problème spécifique. Au lieu de favoriser la discrimination ou la marginalisation, cette imbrication d’appartenances identitaires multiples permet le renforcement du pouvoir d’agir des jeunes femmes francophones. Mots-clés : Dépression, femmes, jeunes, intersectionnalité, services de santé mentale, francophonie minoritaire

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report - Summary. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français. Rapport de recherche - Résumé. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)